Mixed hepatocellular carcinoma-neuroendocrine carcinoma—A diagnostic and therapeutic challenge - Nusrat Jahan; Irfan Warraich; Edwin Onkendi; Sanjay Awasthi (Current Problems in Cancer: Case Reports, 2020)
Mixed hepatocellular carcinoma-neuroendocrine carcinomas (HCC-NECs)11 HCC-NECs: hepatocellular carcinoma-neuroendocrine carcinomas. are rare, and they usually carry a poor prognosis. We report a fascinating case of mixed HCC-NEC — the neuroendocrine component of the tumor was diagnosed retrospectively after discovery of the metastatic neuroendocrine carcinoma (NEC).22 NEC: neuroendocrine carcinoma. A 50-year-old man with cirrhosis underwent resection of a 2.7 cm hepatocellular carcinoma (HCC)33 HCC: hepatocellular carcinoma. at the segment II of the liver. Thirteen months after the surgery he had local recurrence in the liver that was treated with radio-embolization. Eighteen months after the initial diagnosis, he was found to have metastatic NEC in the left shoulder. Later, re-evaluation of the previously resected liver tumor revealed a small focus of tumor cells with neuroendocrine morphology within the tumor, which were negative for HepPar1 and positive for synaptophysin, whereas the majority of the tumor cells were positive for HepPar1 and negative for synaptophysin that reclassified the liver tumor as a combined type of mixed HCC-NEC tumor. Upon discovery of the metastatic NEC, the patient was treated with eight cycles of cisplatin and etoposide with a partial response. Nonetheless, his disease progressed two months after finishing chemotherapy, and he was treated with nivolumab for two cycles. In addition, he received palliative radiation to different skeletal metastases. The patient died of sepsis thirty-three months after the initial diagnosis of liver tumor. In conclusion, mixed HCC-NECs are rare and aggressive— an accurate diagnosis may require a high degree of clinical suspicion and re-evaluation of the pathological specimen, especially when one of the components is scarce. Strategic use of multiple modalities of treatment may prolong the life of patients with this type of aggressive tumor.